2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28986
|View full text |Cite
|
Sign up to set email alerts
|

The Making of an Innovative Engineer: Academic and Life Experiences that Shape Engineering Task and Innovation Self-Efficacy

Abstract: The focus of Mark's research can broadly be described as "pivot thinking," the cognitive aptitudes and abilities that encourage innovation, and the tension between design engineering and business management cognitive styles. To encourage these thinking patterns in young engineers, Mark has developed a Scenario Based Learning curriculum that attempts to blend core engineering concepts with selected business ideas. Mark is also researches empathy and mindfulness and its impact on gender participation in engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Previous research has demonstrated that better learning outcomes of sustainability related challenges are reached when multi-method learning experiences are produced [20]. Additionally, problem-based design challenges and teaching have been connected to increase awareness of societal issues, entrepreneurial intentions and innovation self-efficacy amongst engineering students [11,20,51], highlighting the benefits of generatively applying knowledge within courses. Overall, the students ability to implement the measured sub-themes of sustainability, ethics and collaboration in seven out of the nine sub themes improved statistically significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that better learning outcomes of sustainability related challenges are reached when multi-method learning experiences are produced [20]. Additionally, problem-based design challenges and teaching have been connected to increase awareness of societal issues, entrepreneurial intentions and innovation self-efficacy amongst engineering students [11,20,51], highlighting the benefits of generatively applying knowledge within courses. Overall, the students ability to implement the measured sub-themes of sustainability, ethics and collaboration in seven out of the nine sub themes improved statistically significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Underrepresented minorities (URM) and first generation college (FGC) EMS3.0 graduates at 11 percent and 14 percent are also close to the fractions of the initial EMS 1.0 sample with 14 percent and 16 percent, respectively [3]. The former number (URM fraction) is almost identical to the overall engineering workforce, where the NSF reports 11.5 percent minority groups employed in engineering [1].…”
Section: Demographicsmentioning
confidence: 96%
“…Earlier publications have identified positive effects of targeted education on innovativeness for students studying engineering, e.g. [2][3][4][5][6][7]. In this current research study, we investigate the actual realized innovative behaviors of engineering graduates at the workplace.…”
Section: Introductionmentioning
confidence: 98%
“…Working in an engineering environment as an intern is often a key component of the educational experience of today's engineering students [6]. A 2014 Gallup-Purdue University study of undergraduate alumni found that work and internship experiences in college increased the likelihood of post-graduate full-time employment and greater engagement at work [7].…”
Section: Motivation and Backgroundmentioning
confidence: 99%